Molecular epidemiology of Porcine torovirus (PToV) in Sichuan Province, China: 2011–2013 - Zhou, Lu (BioMed Central, 2014)
BACKGROUND: Porcine torovirus (PToV) is a member of the genus Torovirus which is responsible for gastrointestinal disease in both human beings and animals with particular prevalence in youth. Torovirus infections are generally asymptomatic, however, their presence may worsen disease consequences in concurrent infections with other enteric pathogens. METHODS: A total of 872 diarrheic fecal samples from pigs of different ages were collected from 12 districts of Sichuan Province in the southwest of China. RT-PCR was done with PToV S gene specific primers to detect the presence of PToV positive samples. M gene specific primers were used with the PToV positive samples and the genes were sequenced. A phylogenetic tree was constructed based on the M gene nucleotide sequences from the 19 selected novel Sichuan strains and 21 PToV and BToV M gene sequences from GenBank. RESULTS: A total of 331 (37.96%, 331/872) samples were found to be positive for PToV and the highest prevalence was observed in piglets aged from 1 to 3 weeks old. Through phylogenetic inference the 40 PToV M gene containing sequences were placed into two genotypes (I & II). The 19 novel Sichuan strains of genotype I showed strong correlations to two Korean gene sequences (GU-07-56-11 and GU-07-56-22). Amino-acid sequence analysis of the 40 PToV M gene strains revealed that the M gene protein was highly conserved. CONCLUSIONS: This study uncovered the presence of PToV in Sichuan Province, and demonstrated the need for continuous surveillance PToV of epidemiology.